PERILAKU PRONOMINA PERSONA /ITE/ UNTUK MENYATAKAN ASPEK DAN KEPEMILIKAN DALAM STRUKTUR KALIMAT BAHASA SASAK MASBAGIK - Agustina, Hani (Center of Language and Cultural Studies, 2018)
This study focuses on the behavior of pronouns persona /te/ to express aspects and possessions in the structure of the Masbagic sasak language sentence. This research is descriptive conducted solely based on the facts that exist or the phenomenon that empirically live on the speakers. Researchers describe the data contained in the systematic data related to the problems studied. Data collection referred to the technique of lively cognate and recording techniques. Data were analyzed using intralingual pad method, presenting the result on informal method. The results are pronomina persone has a clitic form of proclitik te- and enclitik -te. When the pronominal persona of the proclical form meets with the verb it will express an aspect and there will be phoneme changes in the verb. When the pronouns persona of the enclosed form meets the nouns it will declare an ownership that there will be an addition of phoneme /n/ if the word attached ends in the vowel and there is no phoneme change in the noun attached if the consonant ends.